Upaya Meningkatkan Life Skills Anak Usia Dini Melalui Metode Bermain Peran Anak Kelompok B TK Marsudirini Desa Kedawung Kecamatan Kroya Kabupaten Cilacap - Wulaningsih, Arum (?ALI?A, 2019)
Classroom Action Research is titled "Efforts to Improve Early Childhood Life Skills Through Role Play Method In My needs Themed Kids Kindergarten Group B village Marsudirini Kedawung Cilacap District Kroya Semester School Year 2012-2013". This study aims to increase life skills of children, with 20 children of students consisting of 12 girls and 8 boys. This classroom action research carried out due to lack of ability of the life skills.The research was conducted by 2 cycles, each cycle of 3 meetings. Data collection methods used in this study is the observation and documentation method, while data analysis techniques using descriptive techniques with a qualitative approach.The results showed an increase in the ability of the child's life skills, increasing from the initial conditions. On initial conditions, students who have achieved specified indicator (BSB) does not exist, while children 5 or 25% developed as expected (BSH), 5 or 25% child begins to develop (MB) and 10 children or 50% undeveloped (BB) who still need guidance.Having conducted action research in the first cycle, the success of the child (BSB) is increasing as many as 14 children or 70%, while 2 children or 10% has reached the indicators of success (BSH), or 20% 4 children begin to develop (MB) and child that reach the indicator (B) is not there.Then the researchers went on to carry out repairs to the second cycle, ability to reach children life skills (BSB) is increasing as many as 16 children or 80%, while 3 children or 15% has reached the indicators of success (BSH), 1 child or 5% begins to develop (MB) and the child who reaches the indicator (BB ) does not exist. If referring to the percentage of success that has ditetapakan, the resulting increase in the ability of the child life skills has achieved a success rate of 80%, then corrective actions have been successful in the second cycle.The recommended follow-up efforts by researchers to parents in order to increase the ability of cooperation and assistance should be given a home visit, then a teacher at the school should pay more attention and to approach them then my friends who are very well developed.